Direct Transesterification/Isomerization/Methoxycarbonylation of Various Plant Oils. (26th September 2012) - Walther, Guido; Martin, Andreas; Köckritz, Angela
Abstract: A selection of plant oils was catalytically transferred into 1, 19‐nonadecanedioate by a direct transesterification, isomerization and methoxycarbonylation under mild conditions using Pd/ o ‐C6 H4 (CH2 P t Bu2 )2 . Additionally, sulfuric acid was demonstrated as being able to substitute methane sulfonic acid as co‐catalyst without any significant loss of activity and selectivity.